Electrochemical device and electronic device
By optimizing the components and content of the electrolyte in lithium-ion batteries, improving the stability of the solid electrolyte interface mask, the problems of high consumption rate and large expansion rate of the electrolyte are solved, and higher energy density and longer service life are achieved.
Patent Information
- Application Number
- CN202510352117.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-06-24
AI Technical Summary
In the process of increasing the energy density, existing lithium-ion batteries face the problems of high electrolyte consumption rate and large battery expansion rate, which affect the safety and service life of the battery.
By controlling the components and content of the electrolyte in the electrochemical device, the film formation quality and stability of the solid electrolyte interface film (SEI film) are optimized, the wetting and kinetics of the electrolyte are improved, and the consumption rate and expansion rate of the electrolyte are reduced.
It improves the stability and self-repair ability of the SEI membrane, reduces the consumption rate of the electrolyte and the expansion rate of the battery, extends the service life of the battery and increases the energy density.
Smart Images

Figure BDA0005326426700000141 
Figure BDA0005326426700000151 
Figure BDA0005326426700000161
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of energy storage, and particularly relates to an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices, such as secondary batteries as rechargeable energy storage devices, can store and release electrical energy through electrochemical reactions, and are key components indispensable for electronic devices, electric vehicles, and energy storage systems. With the continuous iterative upgrade of technology, lithium-ion batteries are widely used due to their high energy density, long cycle life, and environmental friendliness.
[0003] In order to further improve the energy density of lithium-ion batteries, traditional strategies include methods such as increasing the cut-off voltage of the battery, increasing the electrode coating weight, and compaction density. However, while these methods improve the energy density, they often bring some problems. Increasing the cut-off voltage will accelerate the decomposition rate of the electrolyte and may also cause instability of the electrode material, affecting the safety and cycle life of the battery; increasing the coating weight and compaction density will make it difficult for the electrolyte to infiltrate the electrode sheet, and an excessive amount of free electrolyte will affect large-scale production. Currently, industrial production often reduces the electrolyte filling amount, which puts higher requirements on the electrolyte consumption capacity of the battery; and a relatively large coating weight of the active material will exacerbate the increase in the absolute thickness during cycling, resulting in a relatively large swelling rate of the battery cell in the later stage. In recent years, it has been found that by reducing the electrolyte consumption and controlling the swelling rate of the battery cell, not only can a higher volumetric energy density be achieved, but it also helps to maintain the stability inside the battery and extend the service life of the battery. Therefore, reducing the electrolyte consumption rate and the battery swelling rate during cycling has become an important direction for current technological development. Summary of the Invention
[0004] In view of this, this application provides an electrochemical device and an electronic device, which are beneficial to improving the stability of the solid electrolyte interface film (SEI film), improving the swelling rate during cycling, and reducing the electrolyte consumption rate during cycling by controlling the components and content of the electrolyte in the electrochemical device.
[0005] In a first aspect, the present application provides an electrochemical device, including a positive electrode, a negative electrode, and an electrolyte; based on the mass of the electrolyte, the electrolyte includes: ethylene carbonate with a mass content of A%, propylene carbonate with a mass content of B%, diethyl carbonate with a mass content of C%, propyl propionate with a mass content of D%, and ethyl 2,2-difluoroacetate with a mass content of E%; 0.3 ≤ (A + B) / (C + D + E) ≤ 1.25; 20 ≤ A ≤ 30; 20 ≤ E ≤ 30. By controlling the components and mass contents of the electrolyte in the electrochemical device, the present application enables ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), propyl propionate, and ethyl 2,2-difluoroacetate to cooperate with each other, improving the film-forming quality of the solid electrolyte interface film (SEI film), facilitating the formation of a more stable SEI film, enhancing the wettability, kinetics, and oxidation window of the electrolyte, inhibiting side reactions and gas generation problems, improving the swelling rate during the cycling process, and having a lower degree of fragmentation of the SEI film during the cycling process, thereby avoiding excessive consumption of the electrolyte for repairing the SEI film and reducing the consumption rate of the electrolyte during the cycling process.
[0006] In some embodiments, the electrolyte satisfies at least one of the following conditions:
[0007] (1) 22 ≤ A ≤ 26;
[0008] (2) 10 ≤ B ≤ 20;
[0009] (3) 10 ≤ C ≤ 20;
[0010] (4) 10 ≤ D ≤ 20;
[0011] (5) 22 ≤ E ≤ 26;
[0012] (6) 0.4 ≤ (A + B) / (C + D + E) ≤ 0.83.
[0013] When the mass contents of the components of the electrolyte satisfy the above ranges, it can promote better cooperation among the components, further improving the swelling rate during the cycling process and reducing the consumption rate of the electrolyte during the cycling process.
[0014] In some embodiments, the electrolyte includes fluoroethylene carbonate; based on the mass of the electrolyte, the mass content of fluoroethylene carbonate is P%, 8 ≤ P ≤ 15. By using fluoroethylene carbonate in combination with the above electrolyte system, it can further improve the swelling rate during the cycling process and reduce the consumption rate of the electrolyte during the cycling process.
[0015] In some embodiments, the electrolyte includes 1,3,6 - hexanetricarbonitrile; based on the mass of the electrolyte, the mass content of 1,3,6 - hexanetricarbonitrile is Q%, and 1 ≤ Q ≤ 3. In this application, 1,3,6 - hexanetricarbonitrile is used in combination with the above - mentioned electrolyte system, which can bind to the transition metal sites exposed on the surface of the positive electrode, reduce the oxidation tendency of the positive electrode towards the electrolyte, inhibit the deterioration of gas generation during high - temperature storage caused by ethylene carbonate and fluoroethylene carbonate, and reduce the consumption rate of the electrolyte during the cycling process.
[0016] In some embodiments, the electrolyte includes lithium hexafluorophosphate and a second lithium salt, and the second lithium salt includes lithium difluorophosphate and / or lithium tetrafluoroborate; based on the mass of the electrolyte, the mass content of the second lithium salt is T%, and 0.4 ≤ T ≤ 0.6. In this application, the second lithium salt is used in combination with the above - mentioned electrolyte system, which can further improve the gas - generation performance during high - temperature storage and reduce the consumption rate of the electrolyte during the cycling process.
[0017] In some embodiments, the electrolyte includes adiponitrile; based on the mass of the electrolyte, the mass content of adiponitrile is V%, and 1.8 ≤ V ≤ 2.8. In this application, adiponitrile is used in combination with the above - mentioned electrolyte system, which can strengthen the protection of the positive electrode, further improve the consumption rate of the electrolyte during the cycling process and improve the gas - generation performance during high - temperature storage.
[0018] In some embodiments, the electrolyte includes a first component, and the first component includes at least one of 1,2,3 - trifluorobenzene, 1,3,5 - trifluorobenzene, or 1,4 - difluorobenzene; based on the mass of the electrolyte, the mass content of the first component is X%, 4 ≤ X ≤ 6; and / or, 0.15 ≤ X / E ≤ 0.23. In this application, the first component is used in combination with the above - mentioned electrolyte system, which can improve the film - forming quality of the SEI film, inhibit interfacial side reactions, further improve the swelling rate during the cycling process, and reduce the consumption rate of the electrolyte during the cycling process.
[0019] In some embodiments, the electrolyte includes diethyl phenylphosphonate; based on the mass of the electrolyte, the mass content of diethyl phenylphosphonate is Y%, and 0.5 ≤ Y ≤ 1. In this application, diethyl phenylphosphonate is used in combination with the above - mentioned electrolyte system, which can absorb the free radicals generated by the preliminary oxidation of solvent molecules, improve the gas - generation performance during high - temperature storage, and further improve the swelling rate during the cycling process and reduce the consumption rate of the electrolyte during the cycling process.
[0020] In some embodiments, the electrolyte includes lithium trifluoromethanesulfonate; based on the mass of the electrolyte, the mass content of lithium trifluoromethanesulfonate is Z%, and 0.5 ≤ Z ≤ 1. In this application, lithium trifluoromethanesulfonate is used in combination with the above - mentioned electrolyte system, which can improve the film - forming on the negative electrode, inhibit the fragmentation of the interfacial film, further improve the swelling rate during the cycling process, and reduce the consumption rate of the electrolyte during the cycling process.
[0021] In a second aspect, the present application provides an electronic device, including any one of the above-mentioned electrochemical devices. Detailed implementation manners
[0022] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0023] To solve the problems of the prior art, in a first aspect, the present application provides an electrochemical device, including a positive electrode, a negative electrode and an electrolyte; based on the mass of the electrolyte, the electrolyte includes: ethylene carbonate with a mass content of A%, propylene carbonate with a mass content of B%, diethyl carbonate with a mass content of C%, propyl propionate with a mass content of D% and ethyl 2,2-difluoroacetate with a mass content of E%; 0.3 ≤ (A + B) / (C + D + E) ≤ 1.25; 20 ≤ A ≤ 30; 20 ≤ E ≤ 30.
[0024] The inventors found that: compared with linear esters, cyclic esters can better form a passivation film on the electrode surface, but cyclic esters will increase the viscosity of the electrolyte, resulting in difficulty in large-scale use. The present application uses ethylene carbonate and propylene carbonate in combination. Ethylene carbonate has a stronger film-forming ability than propylene carbonate. Therefore, by limiting the mass content of ethylene carbonate in the electrolyte to meet the above range, the initial film-forming quality of the solid electrolyte interface film (SEI film) on the negative electrode surface can be improved, and the self-repair ability of the SEI film can be enhanced, reducing side reactions of the electrolyte. Combining with propylene carbonate can further improve the dissociation ability of the electrolyte for lithium salts, increase the ionic conductivity, and broaden the application temperature window of the electrolyte. At the same time, using diethyl carbonate and propyl propionate can reduce the viscosity of the electrolyte, improve the wetting effect and kinetics of the electrolyte. However, the electrochemical window of these linear esters is narrow. The present application further uses ethyl 2,2-difluoroacetate to increase the oxidation window of the electrolyte. By limiting the mass contents of the above cyclic esters and linear esters to meet the above ratio, the stability of the electrolyte under high-temperature conditions can be improved, side reactions and gas generation of the electrolyte can be reduced, thereby reducing the consumption rate of the electrolyte, and at the same time reducing the swelling rate of the electrochemical device during cycling.
[0025] In some embodiments, 20 ≤ A ≤ 30, preferably 22 ≤ A ≤ 26. For example, A can be 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 or values within the range composed of any two of these values. Controlling the mass content of ethylene carbonate to meet the above range is beneficial for cooperation with other components of the electrolyte, further improving the swelling rate during cycling and reducing the consumption rate of the electrolyte during cycling.
[0026] In some embodiments, 10 ≤ B ≤ 20, preferably 14 ≤ B ≤ 18. For example, B can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or a value within the range formed by any two of these values. Controlling the mass content of propylene carbonate to meet the above range is beneficial for cooperation with other components of the electrolyte, further improving the expansion rate during the cycle and reducing the consumption rate of the electrolyte during the cycle.
[0027] In some embodiments, 10 ≤ C ≤ 20, preferably 12 ≤ C ≤ 16. For example, C can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or a value within the range formed by any two of these values. Controlling the mass content of diethyl carbonate in the electrolyte to meet the above range can better cooperate with other components of the electrolyte, further improving the expansion rate during the cycle and reducing the consumption rate of the electrolyte during the cycle.
[0028] In some embodiments, 10 ≤ D ≤ 20, preferably 14 ≤ D ≤ 18. For example, D can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or a value within the range formed by any two of these values. Controlling the mass content of propyl propionate to meet the above range is beneficial for cooperation with other components of the electrolyte, further improving the expansion rate during the cycle and reducing the consumption rate of the electrolyte during the cycle.
[0029] In some embodiments, 20 ≤ E ≤ 30, preferably 22 ≤ E ≤ 26. For example, E can be 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, or a value within the range formed by any two of these values. Controlling the mass content of ethyl 2,2-difluoroacetate to meet the above range is beneficial for cooperation with other components of the electrolyte, further improving the expansion rate during the cycle and reducing the consumption rate of the electrolyte during the cycle.
[0030] In some embodiments, 0.3 ≤ (A + B) / (C + D + E) ≤ 1.25, preferably 0.4 ≤ (A + B) / (C + D + E) ≤ 0.83. For example, the value of (A + B) / (C + D + E) is 0.3, 0.32, 0.34, 0.39, 0.47, 0.56, 0.67, 0.71, 0.77, 0.86, 0.96, 1.06, 1.11, 1.20, 1.25, or a value within the range formed by any two of these values. When the mass contents of each component of the electrolyte meet the above range, it can promote better cooperation among the components, further improving the expansion rate during the cycle and reducing the consumption rate of the electrolyte during the cycle.
[0031] In some embodiments, the electrolyte includes fluoroethylene carbonate; based on the mass of the electrolyte, the mass content of fluoroethylene carbonate is P%, 8 ≤ P ≤ 15, preferably 10 ≤ P ≤ 14. For example, the mass content of fluoroethylene carbonate can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or a value within the range composed of any two of these values. Adding fluoroethylene carbonate to the electrolyte system of the present application, the higher oxidation potential of fluoroethylene carbonate can reduce the decomposition consumption of the electrolyte at high voltages, and using the higher reduction potential of fluoroethylene carbonate, it is easier to be reduced on the surface of the negative electrode to form an inorganic substance of LiF, and the formed SEI film is thinner, denser and stronger, and is not easily broken during the cycling process, which can reduce the electrolyte consumption for initial swelling and repairing the SEI film, thereby further improving the swelling rate during the cycling process and reducing the consumption rate of the electrolyte during the cycling process.
[0032] In some embodiments, the electrolyte includes 1,3,6 - hexanetricarbonitrile; based on the mass of the electrolyte, the mass content of 1,3,6 - hexanetricarbonitrile is Q%, 1 ≤ Q ≤ 3, preferably 1.3 ≤ Q ≤ 2.7. For example, the mass content of 1,3,6 - hexanetricarbonitrile can be 1%, 1.1%, 1.3%, 1.6%, 1.7%, 1.8%, 2.0%, 2.2%, 2.4%, 2.5%, 2.6%, 2.7%, 2.9%, 3% or a value within the range composed of any two of these values. The inventors found that: as the positive electrode discharges, the valence of transition metal ions will become higher and higher, and the corresponding oxidizing property will become stronger. Adding 1,3,6 - hexanetricarbonitrile to the electrolyte system of the present application, by controlling its mass content to satisfy the above relationship, the strong coordination bond with electron - donating cyano groups contained therein can be utilized, so as to bind to the transition metal sites exposed on the surface of the positive electrode, protect ethylene carbonate and propylene carbonate in the electrolyte system from being oxidized, reduce the oxidation tendency of the positive electrode to the electrolyte, reduce the side reactions and gas - generation problems between the positive electrode and the electrolyte, and further inhibit the deterioration of gas - generation during high - temperature storage caused by ethylene carbonate and fluoroethylene carbonate, and reduce the consumption rate of the electrolyte during the cycling process.
[0033] In some embodiments, the electrolyte includes lithium hexafluorophosphate and a second lithium salt, and the second lithium salt includes lithium difluorophosphate and / or lithium tetrafluoroborate; based on the mass of the electrolyte, the mass content of the second lithium salt is T%, 0.4 ≤ T ≤ 0.6, preferably 0.46 ≤ T ≤ 0.56. For example, the mass content of the second lithium salt can be 0.4%, 0.43%, 0.44%, 0.46%, 0.47%, 0.48%, 0.51%, 0.52%, 0.55%, 0.56%, 0.57%, 0.59%, 0.6% or a value within the range composed of any two of these values. Using the second lithium salt in combination with the above electrolyte system is beneficial in reducing the use of lithium hexafluorophosphate that is unstable at high temperatures on the one hand, and on the other hand, using a mixed lithium salt increases the content and types of negatively charged anions in the electrolyte, which can promote the film-forming effect on the positive electrode interface. By controlling the mass content of the second lithium salt within the above range, it is possible to utilize the oxygen and boron elements contained in lithium difluorophosphate and lithium tetrafluoroborate to form L2O and B-containing substances in the cathode electrolyte interface (CEI film), improve the stability and strength of the CEI film, reduce the fragmentation of the CEI film and the consumption of the electrolyte on the positive electrode side, reduce the side reaction between the positive electrode and the electrolyte, further improve the gas generation performance during high-temperature storage, and reduce the consumption rate of the electrolyte during the cycling process.
[0034] In some embodiments, the electrolyte includes adiponitrile; based on the mass of the electrolyte, the mass content of adiponitrile is V%, 1.8 ≤ V ≤ 2.8, preferably 2.0 ≤ V ≤ 2.6. For example, the mass content of adiponitrile can be 1.8%, 1.9%, 2.0%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8% or a value within the range composed of any two of these values. Adding adiponitrile to the electrolyte system of the present application can supplement the above-mentioned trinitrile, solve the problem that it is difficult to completely cover the active sites on the positive electrode when using trinitrile alone, improve the film-forming quality of the positive electrode interface film, strengthen the protection of the positive electrode. In addition, when used in combination with trinitrile, it can reduce the dissolution of metal elements (such as copper) in the negative electrode current collector when using trinitrile alone, reduce the precipitation of metal elements on the negative electrode surface, improve the stability of the battery system, reduce side reactions, and thus further improve the consumption rate of the electrolyte during the cycling process and improve the gas generation performance during high-temperature storage.
[0035] In some embodiments, the electrolyte includes a first component. The first component includes at least one of 1,2,3-trifluorobenzene, 1,3,5-trifluorobenzene, or 1,4-difluorobenzene; based on the mass of the electrolyte, the mass content of the first component is X%; 4 ≤ X ≤ 6; and / or, 0.15 ≤ X / E ≤ 0.23. For example, the mass content of the first component can be 4%, 4.2%, 4.4%, 4.6%, 4.7%, 4.8%, 5.1%, 5.2%, 5.5%, 5.6%, 5.7%, 5.9%, 6%, or a value within the range formed by any two of these values. In this application, the first component is combined with the above electrolyte system. By controlling its mass content to meet the above range, it is easier for fluorobenzene to adsorb and oxidize to form a film on the graphite surface, and the fluorine atoms in fluorobenzene are used to increase the polarity of the molecules in the electrolyte, inducing the formation of a film at the negative electrode interface for other components, which can improve the stability of the SEI film on the negative electrode surface, inhibit the side reactions with the electrolyte at the negative electrode interface, and thus further improve the swelling rate during the cycling process and reduce the consumption rate of the electrolyte during the cycling process.
[0036] In some embodiments, 0.15 ≤ X / E ≤ 0.23. For example, the value of X / E can be 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, or a value within the range formed by any two of these values. In this application, by controlling the mass content ratio of the first component and ethyl 2,2-difluoroacetate to meet the above relationship, the two can better play their cooperative role, thereby further improving the swelling rate during the cycling process and reducing the consumption rate of the electrolyte during the cycling process.
[0037] In some embodiments, the electrolyte includes diethyl phenylphosphonate; based on the mass of the electrolyte, the mass content of diethyl phenylphosphonate is Y%, 0.5 ≤ Y ≤ 1, preferably 0.6 ≤ Y ≤ 0.8. For example, the mass content of diethyl phenylphosphonate can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or a value within the range formed by any two of these values. Adding diethyl phenylphosphonate to the electrolyte system of this application can capture the free radicals initially generated by the oxidation of solvent molecules using the phosphonic acid group, cut off the oxidation gas generation path of solvent molecules on the cathode side, reduce the side reactions and gas generation of the electrolyte, thereby further improving the gas generation performance during high-temperature storage, and improving the swelling rate during the cycling process and reducing the consumption rate of the electrolyte during the cycling process.
[0038] In some embodiments, the electrolyte includes lithium trifluoromethanesulfonate; based on the mass of the electrolyte, the mass content of lithium trifluoromethanesulfonate is Z%, where 0.5 ≤ Z ≤ 1, preferably 0.6 ≤ Z ≤ 0.8. For example, the mass content of lithium trifluoromethanesulfonate can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, or a value within the range formed by any two of these values. Adding lithium trifluoromethanesulfonate to the electrolyte system of the present application and regulating its mass content to meet the above range can generate a sulfur-containing interface layer through the sulfonic acid structure, strengthen the interface film and make it not easily broken, improve the film-forming quality of the negative electrode interface SEI film, inhibit the breakage of the SEI film, increase the content and types of anions, improve the stability and strength of the CEI film, thereby further improving the swelling rate during the cycle and reducing the consumption rate of the electrolyte during the cycle.
[0039] In the present application, the electrolyte may further include other organic solvents. The present application does not particularly limit the types of other organic solvents, as long as the purpose of the present application can be achieved. For example, it may include, but is not limited to, at least one of ether compounds, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, or trioctyl phosphate or other organic solvents. The above ether compounds may include, but are not limited to, at least one of ethylene glycol dimethyl ether, dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran, or tetrahydrofuran.
[0040] The electrochemical device of the present application is not particularly limited, and it may include any device that undergoes an electrochemical reaction, such as a secondary battery. Hereinafter, the present application will be described by taking a secondary battery as an example in combination with the embodiments of the present application. The secondary battery of the present application is not particularly limited. For example, it may include, but is not limited to: a lithium-ion secondary battery (also referred to as a lithium-ion battery) or a sodium-ion secondary battery.
[0041] In the present application, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector. The above "negative electrode active material layer located on at least one surface of the negative electrode current collector" means that the negative electrode active material layer may be located on one surface of the negative electrode current collector along its own thickness direction, or may be located on two surfaces of the negative electrode current collector along its own thickness direction. It should be noted that the "surface" here may be the entire area of the surface of the negative electrode current collector, or a partial area of the surface of the negative electrode current collector. The present application does not particularly limit it, as long as the purpose of the present application can be achieved.
[0042] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector; the areal density of the negative electrode active material layer is cw g / mm 2 , 8.44×10 -3 ≤cw≤10.38×10 -3 ; 8.44×10 -3 ≤cw≤10.38×10 -3 , preferably 8.99×10 -3 ≤cw≤9.92×10 -3 , for example, cw can be 8.44×10 -3 、8.51×10 -3 、8.62×10 -3 、8.82×10 -3 、8.99×10 -3 、9.11×10 -3 、9.20×10 -3 、9.40×10 -3 、9.62×10 -3 、9.66×10 -3 、9.92×10 -3 、9.93×10 -3 、10.15×10 -3 、10.26×10 -3 、10.38×10 -3 or values within the range formed by any two of these values. Adjusting the areal density of the negative electrode active material layer to meet the above range is beneficial to improving the energy density of the electrochemical device, and in combination with the electrolyte of the present application, can maintain a low battery swelling rate and electrolyte consumption rate during cycling at high energy density.
[0043] The present application does not particularly limit the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or composite current collectors (such as carbon-copper composite current collectors, nickel-copper composite current collectors, titanium-copper composite current collectors, etc.). In the present application, there is no particular limit on the thickness of the negative electrode current collector and the negative electrode active material layer, as long as the purpose of the present application can be achieved.
[0044] The negative electrode active material layer in the present application may further include a negative electrode binder and a negative electrode conductive agent, or the negative electrode active material layer may further include a negative electrode binder, a negative electrode conductive agent, and a thickening agent. There is no particular limitation on the type of the negative electrode binder in the negative electrode active material layer in the present application, as long as the object of the present application can be achieved. For example, the negative electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR), or polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyacrylate, polyvinyl alcohol, or polyacrylic acid. There is no particular limitation on the type of the negative electrode conductive agent in the negative electrode active material layer in the present application, as long as the object of the present application can be achieved. In some embodiments, the negative electrode conductive agent includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, or carbon fiber; metal-based materials, such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. There is no particular limitation on the type of the thickening agent in the present application, as long as the object of the present application can be achieved. For example, the thickening agent may include, but is not limited to, at least one of sodium carboxymethyl cellulose or carboxymethyl cellulose. There is no particular limitation on the mass ratio of the negative electrode active material, the negative electrode conductive agent, the negative electrode binder, and the thickening agent in the negative electrode active material layer in the present application, and those skilled in the art can select according to actual needs as long as the object of the present application can be achieved.
[0045] In the present application, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector. The above "positive electrode active material layer located on at least one surface of the positive electrode current collector" means that the positive electrode active material layer may be located on one surface of the positive electrode current collector along its own thickness direction, or may be located on both surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the "surface" here may be the entire area of the positive electrode current collector surface, or may be a partial area of the positive electrode current collector surface, and there is no particular limitation in the present application as long as the object of the present application can be achieved.
[0046] There is no particular limitation on the positive electrode current collector in the present application as long as the object of the present application can be achieved. For example, the positive electrode current collector may include aluminum foil, aluminum alloy foil, or a composite current collector (such as an aluminum-carbon composite current collector), etc. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer substrate.
[0047] The positive electrode active material layer of the present application contains a positive electrode active material. There is no particular limitation on the type of the positive electrode active material in the present application as long as the object of the present application can be achieved. For example, the positive electrode active material may include lithium nickel cobalt manganese oxide (LiNi 0.90 Co 0.05Mn 0.05 At least one of lithium nickel cobalt manganese oxide (NCM955), NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminate, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium-rich manganese-based material, lithium cobalt oxide (LiCoO2), lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel-type lithium manganate, spinel-type lithium nickel manganate, and lithium titanate. In the present application, the positive electrode active material may further contain a non-metal element. For example, the non-metal element includes at least one of fluorine, phosphorus, boron, chlorine, silicon, or sulfur. In the present application, there is no particular limitation on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the object of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, and the thickness of the single-sided positive electrode active material layer is 30 μm to 120 μm.
[0048] In the present application, the positive electrode active material layer may further include a positive electrode binder and a positive electrode conductive agent. There is no particular limitation on the type of the positive electrode binder in the positive electrode active material layer in the present application, as long as the object of the present application can be achieved. For example, the positive electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyolefins, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, modified polyvinylidene fluoride, modified styrene-butadiene rubber (SBR), or polyurethane. In some embodiments, the polyolefin binder includes at least one of polyethylene, polypropylene, polyacrylate, polyvinyl alcohol, or polyacrylic acid.
[0049] There is no particular limitation on the type of the positive electrode conductive agent in the positive electrode active material layer in the present application, as long as the object of the present application can be achieved. In some embodiments, the positive electrode conductive agent includes carbon-based materials, such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, or carbon fiber; metal-based materials, such as metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives; or mixtures thereof. There is no particular limitation on the mass ratio of the positive electrode active material, the positive electrode conductive agent, and the positive electrode binder in the positive electrode active material layer in the present application, and those skilled in the art can select according to actual needs as long as the object of the present application can be achieved. For example, the loading amount of the positive electrode active material in the positive electrode sheet is 4.0 mg / cm 2 to 10.0 mg / cm 2 .
[0050] To prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode of the secondary battery. In this case, the electrolyte of the present application usually penetrates into the separator for use.
[0051] There are no particular restrictions on the material and shape of the separator membrane, as long as the effects of this application are not significantly impaired. The separator membrane can be a resin, glass fiber, inorganic substance, etc. formed from a material that is stable to the electrolyte of this application. In some embodiments, the separator membrane includes a porous sheet or a non-woven fabric-like substance with excellent liquid retention properties. Examples of the material of the resin or glass fiber separator membrane can include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyethersulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The above materials of the separator membrane can be used alone or in any combination.
[0052] The separator membrane can also be a material formed by laminating the above materials. Examples include, but are not limited to, a three-layer separator membrane laminated in the order of polypropylene, polyethylene, and polypropylene.
[0053] Examples of the material of the inorganic substance can include, but are not limited to, oxides such as alumina and silica, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.). The form of the inorganic substance can include, but is not limited to, granular or fibrous.
[0054] The form of the separator membrane can be a thin film form. Examples include, but are not limited to, non-woven fabric, woven fabric, microporous membrane, etc. In the thin film form, the pore diameter of the separator membrane is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In addition to the above independent thin film-like separator membrane, the following separator membrane can also be used: a separator membrane formed by forming a composite porous layer containing the above inorganic substance particles on the surface of the positive electrode and / or negative electrode by using a resin-based binder. For example, a separator membrane formed by using a fluororesin as a binder to form a porous layer on both sides of the positive electrode with 90% of the alumina particles having a particle size less than 1 μm.
[0055] The thickness of the separator membrane is arbitrary. In some embodiments, the thickness of the separator membrane is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the separator membrane is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the separator membrane is within the above range, insulation and mechanical strength can be ensured, and the rate performance and energy density of the secondary battery can be ensured.
[0056] The secondary battery of this application further includes a packaging bag for accommodating the positive electrode, negative electrode, separator, and electrolyte, as well as other components known in the art in the secondary battery. This application does not limit the above other components. This application has no particular restrictions on the packaging bag and can be a packaging bag well known in the art as long as the purpose of this application can be achieved.
[0057] The preparation process of the secondary battery of the present application is well-known to those skilled in the art, and the present application has no special limitations. For example, it may include, but is not limited to, the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, and winding, folding, etc. as needed to obtain a wound electrode assembly, placing the electrode assembly in a packaging bag, injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, and then fixing the four corners of the entire laminated structure with tape to obtain a laminated electrode assembly, placing the electrode assembly in a packaging bag, injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, an overcurrent protection element, a guide plate, etc. can be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging / discharging.
[0058] In a second aspect, the present application provides an electronic device including any one of the above electrochemical devices.
[0059] The use of the electrochemical device of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. In some embodiments, the electronic device of the present application includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a headset stereo, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a minidisc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, an automobile, a motorcycle, a moped, a bicycle, a lighting fixture, a toy, a game console, a clock, a power tool, a flash, a camera, a large household battery, and a lithium-ion capacitor, etc.
[0060] The solution of the present application will be described below by taking a lithium-ion battery as an example in combination with the following specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from ordinary commercially available products, and the devices or equipment used are all purchased from conventional market sales channels. Various tests and evaluations are carried out according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0061] Testing method
[0062] Battery swelling rate test:
[0063] At room temperature (25 °C), the battery is charged at a constant current of 1C to 4.55V, and then charged at a constant voltage of 4.55V until the current is less than 50mA. The initial thickness of the battery is measured using a micrometer. Then, the battery is cycled 500 times under the following charge and discharge conditions: discharged at a constant current of 0.5C to 3V, allowed to stand for 5 minutes, charged at a constant current of 1C to 4.55V, and then charged at a constant voltage of 4.55V until the current is less than 50mA. After the 500th charge, the thickness of the battery after cycling is measured at the same position using a micrometer. Battery swelling rate (%) = (thickness after cycling - initial thickness) / initial thickness × 100%.
[0064] Electrolyte consumption rate test:
[0065] At room temperature (25 °C), the battery is charged at a constant current of 1C to 4.55V, and then charged at a constant voltage of 4.55V until the current is less than 50mA. After standing for 5 minutes, it is discharged at a constant current of 0.5C to 3V, and the initial discharge capacity of the battery is recorded. Then, the battery is cycled under the above charge and discharge conditions, and the number of cycles when the battery capacity decays to 60% of the initial capacity is recorded. The longer the number of cycles required to decay to 60% of the initial capacity, the slower the electrolyte consumption rate in the battery.
[0066] High-temperature storage gas generation performance test:
[0067] The oven temperature is adjusted to room temperature (25 °C), and the battery is allowed to stand at this temperature for 60 minutes; the battery is charged at a constant current of 1C to 4.55V, and then charged at a constant voltage of 4.55V until the current is less than 50mA, and the initial thickness of the battery at room temperature is recorded.
[0068] The battery is transferred to an oven at 60 °C for storage, and the number of cycle days
D (days)
[0069] Example 1-1
[0070] <Preparation of electrolyte>
[0071] In a dry argon atmosphere glove box, lithium hexafluorophosphate (LiPF6) as a supporting electrolyte is dissolved in a solution containing ethyl acetate, ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate, and 2,2-difluoroethyl acetate. Based on the mass of the electrolyte, the mass content of lithium hexafluorophosphate is 10%, and the mass contents of ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate, and 2,2-difluoroethyl acetate are as shown in Table 1 below, with the balance being ethyl acetate.
[0072] <Preparation of Negative Electrode Plate>
[0073] Mix silicon-carbon particles and graphite particles in a mass ratio of 1:4 to obtain the negative electrode active material; mix the negative electrode active material, the negative electrode conductive agent Super P, the thickening agent sodium carboxymethylcellulose (CMC), and the negative electrode binder polymethyl acrylate (PMA) in a mass ratio of 95:2:1:2, then add deionized water as a solvent to formulate a negative electrode slurry with a solid content of 60 wt%. Coating the negative electrode slurry evenly on a negative electrode current collector copper foil with a thickness of 10 μm, drying, cold pressing, and welding the tab to obtain the negative electrode plate. In the negative electrode plate, the areal density of the negative electrode active material layer is 9.62×10 -3 g / mm 2 .
[0074] <Preparation of Positive Electrode Plate>
[0075] Mix the positive electrode active material lithium cobalt oxide (LiCoO₂), the positive electrode binder polyvinylidene fluoride (PVDF), and the positive electrode conductive agent Super P in a mass ratio of 97:1.6:1.4, add N-methylpyrrolidone (NMP) as a solvent to formulate a slurry with a solid content of 75 wt%, and stir evenly. Coating the positive electrode slurry evenly on a positive electrode current collector aluminum foil with a thickness of 10 μm, drying, cold pressing, and welding the tab to obtain the positive electrode plate.
[0076] <Separator>
[0077] Use a polyethylene-polypropylene composite film with a thickness of 7 μm.
[0078] <Preparation of Lithium-Ion Battery>
[0079] Stack the above-prepared positive electrode plate, separator, and negative electrode plate in sequence, with the separator in the middle of the positive electrode plate and the negative electrode plate to play a blocking role, and then wind to obtain an electrode assembly. After welding the tab, place the electrode assembly in an aluminum-plastic film packaging shell, dry it in a vacuum oven at 85 °C for 12 hours to remove moisture, inject the above-prepared electrolyte, and obtain a lithium-ion battery through processes such as vacuum packaging, standing, and formation.
[0080] In Table 1, the main difference between each example and the comparative example compared with Example 1-1 is that the parameters shown are adjusted according to Table 1.
[0081] Table 1
[0082]
[0083]
[0084] As can be seen from Table 1, in this application, by controlling the electrolyte to include ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate, and ethyl 2,2-difluoroacetate, and controlling the mass content of each component to satisfy 0.3 ≤ (A + B) / (C + D + E) ≤ 1.25, 20 ≤ A ≤ 30, and 20 ≤ E ≤ 30, the components can cooperate with each other to improve the swelling rate during cycling and reduce the consumption rate of the electrolyte during cycling. In particular, when the mass content of each component is controlled to satisfy 22 ≤ A ≤ 26, 22 ≤ E ≤ 26, and / or 0.4 ≤ (A + B) / (C + D + E) ≤ 0.83, the swelling rate during cycling can be further improved and the consumption rate of the electrolyte during cycling can be reduced.
[0085] The main difference between each example in Table 2 and Example 1-1 is that the electrolyte is prepared by a method including the following steps:
[0086] In a dry argon atmosphere glove box, vinylene carbonate and lithium hexafluorophosphate are dissolved in a solution containing ethyl acetate, ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate, and ethyl 2,2-difluoroacetate. Based on the mass of the electrolyte, the mass content of lithium hexafluorophosphate, ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate, and ethyl 2,2-difluoroacetate is the same as that in Example 1-1, and the mass content of vinylene carbonate is as shown in Table 2, with the balance being ethyl acetate.
[0087] Table 2
[0088]
[0089] As can be seen from Table 2, in this application, by adding vinylene carbonate to the electrolyte and controlling the mass content of vinylene carbonate to be 8% to 15%, preferably 10% to 14%, the swelling rate during cycling can be further improved and the consumption rate of the electrolyte during cycling can be reduced.
[0090] The main difference between each example in Table 3 and Example 1-10 is that the electrolyte is prepared by a method including the following steps:
[0091] In a dry argon atmosphere glove box, 1,3,6-hexanetricarbonitrile, a second lithium salt, adiponitrile, or diethyl phenylphosphonate is dissolved in a solution containing ethyl acetate, ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate, and ethyl 2,2-difluoroacetate. Based on the mass of the electrolyte, the mass content of ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate, and ethyl 2,2-difluoroacetate is the same as that in Example 1-10, and the mass content of 1,3,6-hexanetricarbonitrile, the second lithium salt, adiponitrile, and diethyl phenylphosphonate is as shown in Table 3, with the balance being ethyl acetate.
[0092] Table 3
[0093]
[0094]
[0095] As can be seen from Table 3, in the present application, 1,3,6 - hexanetricarbonitrile, a second lithium salt, adiponitrile or diethyl phenylphosphonate is respectively added to the electrolyte, and its mass content is adjusted to meet the above range, which can further improve the swelling rate and the consumption rate of the electrolyte during the cycle, and also improve the gas generation performance during high - temperature storage.
[0096] In particular, when the electrolyte simultaneously includes 1,3,6 - hexanetricarbonitrile, a second lithium salt, adiponitrile and diethyl phenylphosphonate, and its mass content is adjusted to meet the above range, it can further improve the swelling rate, the consumption rate of the electrolyte during the cycle and the gas generation performance during high - temperature storage in cooperation with other components.
[0097] Compared with Examples 1 - 10, the main difference in Examples 4 - 1 to 4 - 14 in Table 4 is that the electrolyte is prepared by a method including the following steps:
[0098] In a dry argon - atmosphere glove box, the first component and lithium trifluoromethanesulfonate are dissolved in a solution containing ethyl acetate, ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate and 2,2 - difluoroethyl acetate. Based on the mass of the electrolyte, the mass contents of ethylene carbonate, propylene carbonate, diethyl carbonate, propyl propionate and 2,2 - difluoroethyl acetate are the same as those in Examples 1 - 10, the mass contents of the first component and lithium trifluoromethanesulfonate are as shown in Table 4, and the balance is ethyl acetate. In addition, on the basis of Example 3 - 19, Example 4 - 15 prepares the electrolyte according to the above method, and the mass contents of the first component and lithium trifluoromethanesulfonate are as shown in Table 4.
[0099] Table 4
[0100]
[0101] As can be seen from Table 4, in the present application, the first component or lithium trifluoromethanesulfonate is respectively added to the electrolyte, and its mass content is adjusted to meet the above range, which can further improve the swelling rate during the cycle and reduce the consumption rate of the electrolyte during the cycle.
[0102] In particular, when the electrolyte simultaneously includes the first component and lithium trifluoromethanesulfonate, and its mass content is adjusted to meet the above range, it can further improve the swelling rate during the cycle and reduce the consumption rate of the electrolyte during the cycle in cooperation with other components.
[0103] The above are only the preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent replacements, improvements, etc. made within the principles of the present application shall be included within the protection scope of the present application.
Claims
1. An electrochemical device, characterized in that: including a positive electrode, a negative electrode and an electrolyte; Based on the mass of the electrolyte, the electrolyte comprises: ethylene carbonate with a mass content of A%, propylene carbonate with a mass content of B%, diethyl carbonate with a mass content of C%, propyl propionate with a mass content of D%, and ethyl 2,2-difluoroacetate with a mass content of E%; 0.3≤(A+B) / (C+D+E)≤1.25; 20≤A≤30; 20≤E≤30.
2. The electrochemical device according to claim 1, characterized in that The electrolyte satisfies at least one of the following conditions: (1)22≤A≤26; (2)10≤B≤20; (3)10≤C≤20; (4)10≤D≤20; (5)22≤E≤26; (6)0.4≤(A+B) / (C+D+E)≤0.
83.
3. The electrochemical device according to claim 1 or 2, characterized in that: The electrolyte includes fluoroethylene carbonate; based on the mass of the electrolyte, the mass content of the fluoroethylene carbonate is P%, 8≤P≤15.
4. The electrochemical device according to claim 1 or 2, characterized in that: The electrolyte includes 1,3,6-hexanetrinitrile; Based on the mass of the electrolyte, the mass content of the 1,3,6-hexanetrinitrile is Q%, and 1≤Q≤3.
5. The electrochemical device according to claim 4, characterized in that The electrolyte includes lithium hexafluorophosphate and a second lithium salt, and the second lithium salt includes lithium difluorophosphate and / or lithium tetrafluoroborate; Based on the mass of the electrolyte, the mass content of the second lithium salt is T%, and 0.4≤T≤0.
6.
6. The electrochemical device according to claim 4, characterized in that The electrolyte includes adiponitrile; Based on the mass of the electrolyte, the mass content of adiponitrile is V%, and 1.8≤V≤2.
8.
7. The electrochemical device according to claim 1 or 2, characterized in that: The electrolyte includes a first component, the first component includes at least one of 1,2,3-trifluorobenzene, 1,3,5-trifluorobenzene or 1,4-difluorobenzene; Based on the mass of the electrolyte, the mass content of the first component is X%; 4≤X≤6; and / or, 0.15≤X / E≤0.
23.
8. The electrochemical device according to claim 1 or 2, characterized in that: The electrolyte includes diethyl phenylphosphonate; Based on the mass of the electrolyte, the mass content of diethyl phenylphosphonate is Y%, and 0.5≤Y≤1.
9. The electrochemical device according to claim 1 or 2, characterized in that: The electrolyte includes lithium trifluoromethanesulfonate; Based on the mass of the electrolyte, the mass content of the lithium trifluoromethanesulfonate is Z%, and 0.5≤Z≤1.
10. An electronic device, characterized in that: An electrochemical device comprising any one of claims 1 to 9.